Pembuatan Basis Data Spasial Desa Perkotaan (Urban Village) Melalui Partispasi Masyarakat - Harimudin, Jamal; Alfirman, Alfirman; Fitriani, Fitriani (Jurnal Ilmiah Pangabdhi, 2023)
Increasing the knowledge and capacity of village officials in understanding and managing spatial data bases in the urban village is an important part of the one map program. The purpose of the service is (1) knowing the administrative boundaries of Melai Village, Murhum District; (2) have an understanding of participatory-based spatial databases for tourism objects in Melai Urban Village, Murhum District. The method used is participatory based. The results of this trial are that participants are able to determine the boundaries of the urban village and the participants show the Melai Urban Village tourism object and then produce the results from the joint consultation.